MEDIA ANIMASI DAN IKLAN LAYANAN MASYARAKAT DALAM UPAYA PENINGKATAN PENGETAHUAN TENTANG PENCEGAHAN STUNTING PADA REMAJA DI SMA NEGERI 1 NGORO KABUPATEN MOJOKERTO - Asih Media Yuniarti; Mukhammad Himawan Saputra; Dwi Helynarti Syurandhari; Intan Arya Putri Dwi Pandini (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Stunting is still a major health problem in Indonesia. The low knowledge of adolescents about the importance of proper nutrition as prospective parents can increase the risk of children born experiencing stunting. The research objective was to determine the effect of animation and public advertising services on increasing knowledge about stunting prevention in adolescents at SMA Negeri 1 Ngoro. The study used the Quasi-Experimental Design method, with a population of 202 students using a simple random sampling technique to obtain a sample of 84 students. The results showed that half (50%) of the respondents had sufficient knowledge before being given animation, almost all (85.7%) of the respondents had good knowledge after the animation was given while the majority (59.5%) of respondents had good knowledge before being given Public Advertising services and almost all (95.2%) of respondents have good knowledge after being given public advertising services. The results showed that animation and public service advertisements affected increasing adolescent knowledge (P value = 0.000), and public service advertisements were able to increase knowledge higher (P value = 0.001). Animation and public advertising services are media that are preferred by adolescents, so it is recommended to convey health messages